PHONON-SPECTRA OF RANDOMLY DISORDERED SYSTEM - Lavarda, Francisco Carlos [UNESP]; Laks, B. (Elsevier B.V., 1991)
We study the phonon density of states of a three dimensional disordered mixed crystal NaCl(x)Br1-x. The phonon structure is obtained by using a cluster method based on a continued fraction expansion of the Green function. The proposed dynamic model includes only short range interactions (first and second neighbors) but supports some qualitative features of the constituents binary alloys.